Multi-objective optimization for stochastic computer networks using NSGA-II and TOPSIS - Lin, Yi-Kuei; Yeh, Cheng-Ta (European journal of operational research, 2012)
► Find the optimal network line assignment with maximal network reliability and minimal total cost. ► Evaluate network reliability in terms of MPs and RSDP. ► An approach based on NSGA-II and TOPSIS is proposed to solve the multi-objective problem. ► Focus on practical computer networks to implement the transmission line assignment. Network reliability is a performance indicator of computer/communication networks to measure the quality level. However, it is costly to improve or maximize network reliability. This study attempts to maximize network reliability with minimal cost by finding the optimal transmission line assignment. These two conflicting objectives frustrate decision makers. In this study, a set of transmission lines is ready to be assigned to the computer network, and the computer network associated with any transmission line assignment is regarded as a stochastic computer network (SCN) because of the multistate transmission lines. Therefore, network reliability means the probability to transmit a specified amount of data successfully through the SCN. To solve this multiple objectives programming problem, this study proposes an approach integrating Non-dominated Sorting Genetic Algorithm II (NSGA-II) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). NSGA-II searches for the Pareto set where network reliability is evaluated in terms of minimal paths and Recursive Sum of Disjoint Products (RSDP). Subsequently, TOPSIS determines the best compromise solution. Several real computer networks serve to demonstrate the proposed approach.